2012
DOI: 10.1016/j.otsr.2012.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Axial rotation of the first metatarsal head in a normal population and hallux valgus patients

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
2
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 11 publications
1
57
2
6
Order By: Relevance
“…This would lead to the inaccurate conclusion that in feet with HAV, the hallux is in a frontal plane valgus position and the metatarsal is in a frontal plane varus position. It is improper to apply the asserted normal mechanics to the position of the first ray in a bunion deformity, because the valgus (pronated) rotational position has been clearly delineated in the published data (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would lead to the inaccurate conclusion that in feet with HAV, the hallux is in a frontal plane valgus position and the metatarsal is in a frontal plane varus position. It is improper to apply the asserted normal mechanics to the position of the first ray in a bunion deformity, because the valgus (pronated) rotational position has been clearly delineated in the published data (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…Available investigations regarding bunionaffected feet have reported both the first metatarsal and the phalangeal components of the first metatarsal phalangeal joint (MTPJ) in a valgus (pronated) position (1)(2)(3)(4). Studies reporting the observed frontal plane position of the first metatarsal include both qualitative and quantitative descriptions.…”
mentioning
confidence: 99%
“…Chang et al 29 , em 1984, discutem em um estudo caso-controle as diversas Mortier et al 60 , em 2012, realizam um estudo radiográfico em 100 pacientes com hálux valgo, utilizando uma técnica radiográfica axial, para avaliar a pronação da cabeça do 1º metatarsal e a posição dos sesamóides. Discutem a importância de elevar o calcâneo e as articulações metatarsofalângicas para evitar a sobreposição das imagens.…”
Section: Estudos Radiográficos Do Plano Coronalunclassified
“…Muito se discute sobre a associação do hálux valgo com a instabilidade da 1ª articulação tarsometatarsal nos planos sagital e coronal, inclusive uma relação de causalidade entre a deformidade e a instabilidade, mas ainda não há consenso entre os autores [53][54][55][56]60,65,72,73 .…”
Section: Caracterização Da Casuística Utilizadaunclassified
“…Tasa de mujeres en dife-rentes estudios en relación al hallux valgus, apreciando un alto predominio de sexo femenino en los mismos. Thomas & Barrington 10 Hallux valgus 90 Thordarson et al 37 Resultados quirúrgicos 92 Thordarson et al 59 Resultados quirúrgicos 100 Ullot et al 60 Hallux valgus juvenil 78 Villas et al 30 Artrosis plantar 92 Wukich et al 61 Osteotomía de apertura basal 69 Coughlin & Shurnas 62 Hallux valgus 92 Thordarson et al 63 Resultados quirúrgicos 92 Neese & Zelent 64 Osteotomía de Mau--Reverdin 85 Mortier et al 65 Rotación del primer metatarsiano 94 Menz et al 66 Calzado en pacientes mayores 68 Schneider & Knahr 67 Expectativas quirúrgicas 87 Menz et al 68 Caídas en relación a problemas de los pies 68 Kristen et al 69 Osteotomía de scarf 91 Dawson et al 70 Calidad de vida 66 Rose et al 71 Osteotomía de alargamiento de scarf 90 De Prado et al 72 Corrección percutánea 97 Larholt & Kilmartin 73 Osteotomía de scarf 89…”
Section: Historia Naturalunclassified